Status of grey seals (Halichoerus grypus) in Norway - Nilssen, Kjell Tormod; Haug, Tore (NAMMCO Scientific Publications, 2007)
During the period September-December in 2001-2003, ship based surveys of grey seal (Halichoerus grypus) pups, including tagging, counting and staging of pups, were conducted along the Norwegian coast. All known and other potential breeding areas were surveyed from Rogaland county in the south to Finnmark county in the north. Most of the breeding sites were surveyed only once, but some sites were surveyed 2-4 times. The investigations resulted in a total minimum estimate of 1,159 grey seal pups born in Norwegian waters. Nordland county was the most important breeding area where about 50% of the pups were born. Total population estimates were derived from the recorded number of pups born using a range of multipliers (4.0-4.7), based on observed annual growth rates of approximately 7-12% in other grey seal populations. This gave a total estimate of about 5,800-6,600 grey seals including pups in Norwegian waters. However, the total pup production was probably underestimated due to only one pup count in most of the breeding sites. Observed mean pup mortality was 1.1% during the breeding season along the Norwegian coast.